Implications of Demographic Change in Least Developed Countries - Majewska, Julia (Implikacje zmian demograficznych w krajach najsłabiej rozwiniętych, 2022)
Demographic changes are one of the determinants shaping the global economy. Due to the growing population, the analysis of demographic changes in developed and developing countries is crucial. The aim of the article was to identify changes in the demographic structure of the least developed countries, and to assess the impact of demographic trends on the world economy. The study examines selected demographic trends in the least developed countries, including positive population growth, increase in life expectancy and in the number of children aged 0-14. The possible consequences for population growth in LDCs were also indicated. Based on the analysis of the literature and quantitative data, a possible increase in net migration from the LDCs and the probability of cultural problems in the host countries were identified. The research methods used in the article were the analysis of the literature and the method of inference.
Ekonomia XXI Wieku = Economics of the 21st Century, 2022, Nr 25, s. 28-38
Keywords: LDCs; demographics; population; kraje najsłabiej rozwinięte; demografia; populacja